Day surgery nurses' selection of patient preoperative information. Issue 1 (19th September 2016) - Mitchell, Mark
Abstract : Aims and objectives: To determine selection and delivery of preoperative verbal information deemed important by nurses to relay to patients immediately prior to day surgery. Background: Elective day‐case surgery is expanding, patient turnover is high and nurse–patient contact limited. In the brief time‐frame available, nurses must select and precisely deliver information to patients, provide answers to questions and gain compliance to ensure a sustained, co‐ordinated patient throughput. Concise information selection is therefore necessary especially given continued day surgery expansion. Study design: Electronic questionnaire. Methods: A survey investigating nurses' choice of patient information prior to surgery was distributed throughout the UK via email addresses listed on the British Association of Day Surgery member's website (January 2015–April 2015). Results: Participants were requested to undertake the survey within 2–3 weeks, with 137 participants completing the survey giving a 44% response rate. Verbal information deemed most important by nurses preoperatively was checking fasting time, information about procedure/operation, checking medication, ensuring presence of medical records/test results and concluding medical investigations checks. To a lesser extent was theatre environment information, procedure/operation start time and possible time to discharge. Significant differences were established between perceived importance of information and information delivery concerning the procedure/operation and anaesthesia details. Conclusion: Nurses working with competing demands and frequent interruptions, prioritised patient safety information. Although providing technical details during time‐limited encounters, efforts were made to individualise provision. A more formal plan of verbal information provision could help ease nurses' cognitive workload and enhance patient satisfaction. Relevance to clinical practice: This study provides evidence that verbal information provided immediately prior to day surgery may vary with experience. Nurse educators and managers may need to provide greater guidance for such complex care settings as delivery of increasingly technical details during brief encounters is gaining increasing priority.